CERAMIC-ON-CERAMIC TOTAL HIP ARTHROPLASTY IN YOUNG PATIENTS WITH FEMORAL-HEAD OSTEONECROSIS - SHORTTERM RESULTS - Tudor Sorin Pop; Sandor-Gyorgy Zuh; Margit Hidi; Attila Vass; Istvan Gergely (European Scientific Journal, ESJ, 2015)
Aim: the increasing number of total hip arthroplasties in case of young, physically active patients means an increasing number of revision surgeries as well. For these patients the use of ceramic bearings could be an appropriate solution because of its reduced wear and a predicted longer lifetime. In this paper we would like to present our short experiences with non-cemented, ceramic-on-ceramic total hip prosthesis, in case of young patients. Materials and Methods: between January 2011 and December 2012, 32 hip arthroplasties were performed in case of 31 young patients diagnosed with avascular necrosis of the femoral head. The clinical and radiological follow-up of these patients was carried out for an average of 1,5 year. The average age was 47 years (25-51) in the moment of the surgery. The clinical assessment of the patients were carried out by the Harris Hip Score and Visual Analog Scale, performed before and 3, 6, 12 month after surgery. The radiological evaluation was based on the anteroposterior and axial radiographs performed at the above mentioned time points. Results: in each cases the bony ingrowth of the prosthesis took place. No stressshielding phenomenon was observed at the proximal part of the femur. In one case at six month control X-ray we noticed the damage of the ceramic insert and no further complications were observed. The patient refused the revision surgery for now. Conclusions: the fourth-generation ceramic component for non-cemented endoprosthesis used in case of young patients has very good early clinical and radiological results.